Assessment of Green Chemistry Competencies and Training Needs Among Secondary School Chemistry Teachers - Toyin Eunice Owoyemi; Ayotomiwa Abel Akinde (Journal of Research in Environmental and Science Education, 2026)
Green chemistry, a framework for designing safer chemical processes and reducing environmental hazards, is increasingly essential in science education. However, in Nigeria, secondary school chemistry curricula lack adequate integration of green chemistry principles, and teachers remain underprepared to teach these concepts. This study assessed the green chemistry competencies and training needs of secondary school chemistry teachers in Lagos State to inform targeted professional development and policy reform. Employing a sequential mixed-methods design, data were collected from 43 chemistry teachers using structured questionnaires and semi-structured interviews. Quantitative data captured teachers’ self-reported practices, understanding of green chemistry principles, and perceived training needs, while qualitative interviews explored classroom implementation and contextual challenges. Findings revealed a significantly low level of green chemistry practice, with over 85% of teachers reporting that they never or rarely incorporated core principles such as atom economy, waste reduction, or energy efficiency into instruction. Teachers demonstrated limited understanding of the twelve principles of green chemistry and low confidence in applying them, particularly in designing green experiments, selecting environmentally friendly reagents, and teaching sustainable product design. Key barriers identified included limited curricular guidance, lack of resources, and insufficient training opportunities. A needs analysis highlighted six critical competency areas requiring urgent intervention, including foundational knowledge, lesson integration, laboratory practices, waste management, and application of advanced sustainability concepts. The study concludes that comprehensive, context-specific professional development and curriculum reforms are vital to bridge current competency gaps and enhance sustainable chemistry instruction. These findings offer actionable insights for policymakers, curriculum developers, and teacher educators seeking to embed environmental responsibility in science education.